Institutional Drivers of Customer Loyalty in Islamic Banks: A Structural Model of Customer Loyalty from Educational Organizations in Indonesia - Muh. Abdi Imam; Erwin; Dini Nurpratiwi; Ahmad Nouruzzamand; Jabaluddin Hamid; Hajar Dewantara; Mujahidin; Sumarwadji, Hafid (Universitas Muhammadiyah Malang, 2026)
This study aims to analyze and identify factors influencing customer loyalty in Islamic banks, focusing on educational organizations in Indonesia. Customer loyalty is a crucial aspect for the sustainability of Islamic banks, especially amidst increasingly fierce competition in the banking industry. This study employed a quantitative research design, utilizing primary data collected via structured questionnaires. Quantitative approaches are well-suited for testing hypotheses and analyzing relationships between variables statistically. The questionnaires were distributed both in-person and online to Islamic bank customers from educational organizations in Indonesia over a four-week period with a final sample of 101 respondents. The data were analyzed using SEM-PLS to test the measurement and structural models. The results indicate that service quality significantly influences customer satisfaction, brand image, and loyalty. While customer satisfaction affects brand image, it does not directly influence loyalty, whereas brand image plays a key role in driving customer loyalty. Theoretically, this study contributes to the Islamic banking literature by confirming the mediating roles of brand image and customer satisfaction and offering a foundation for future research on loyalty in institutional and sharia-based financial contexts. This study provides practical insights for Islamic bank management to enhance customer loyalty through improved service quality, trust building, and consistent implementation of sharia principles.